STRATEGI GURU PAI DI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMKN PASIRIAN LUMAJANG - Muhammad Havid; mohammad Hanif; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The teacher's strategy is a general teaching approach that applies in various fields of material and is used to meet various learning objectives in schools. The process of teaching and learning also needs a strategy in learning Islamic religious education at SMKN Pasirian Lumajang so that it can convey learning in class according to the teacher's strategy. The background of the problem in the teacher's strategy in learning Islamic religious education, planning in learning, implementing and evaluating learning in the classroom during learning (2) In this thesis research, the author uses a qualitative approach because this research is a form of descriptive research. qualitative. It is said to be descriptive qualitative because this study aims to describe the results of data processing in the form of words, general descriptions that occur in the field. In the method I took, the qualitative research method used three stages, namely the interview, observation and documentation methods. Based on the results of the research that has been carried out, the researcher concludes regarding the PAI Teacher Strategy in Islamic Religious Education Learning at SMKN Pasirian Lumajang. Islamic Religious Education learning planning at SMKN Pasirian Lumajang uses the following methods: 1) RPP (Learning Implementation Plan), 2) Semester Program, 3) Annual Program (Evaluation or Assessment) 4) Syllabus,